EFEITOS DA CARÃŠNCIA DE CÃLCIO, BORO E ZINCO SOBRE A PRODUTIVIDADE DE SOJA (Glycine Max (L.) MERRILL CV. SANTA ROSA - Rodrigues, Selma Dzimidas; Moraes, JosÃ© Antonio ProenÃ§a Vieira de; Rodrigues, JoÃ£o Domingos; Ono, Elizabeth Orika; Delachiave, Maria Elena Aparecida; Pedras, JosÃ© Figueiredo (REVISTA DE AGRICULTURA, 2015)
EFEITOS DA CARÃŠNCIA DE CÃLCIO, BORO E ZINCO SOBRE A PRODUTIVIDADE DE SOJA (Glycine Max (L.) MERRILL CV. SANTA ROSA